AAPHD 62nd Annual Session Abstracts - Robert E. Smith, ODs*, Victor Badner, DMD, MPH (Blackwell Synergy, 2000)
The objective of this study was to develop an index which will easily and inexpensively identdy pregnant women whose unborn children wiU be at high risk for early childhood caries. This pilot study identified mothers (n=29) whose 3- to 5-year-old children have at least one carious or restored surface, and compared them to a control group (n=31) whose children are caries free. Independent variables included country of origin, education, ethnicity, age, socioeconomic status, sugar consumption, plaque, previous caries experience, active caries, and streptococcus mutans (sm). Sm (72% cases, 16% controls), active decay (mean: cases 35, controls 26) and sugar consumption index (mean: cases 36.4, controls 24.9) were the three indicators which were sigruficant in differentiating the two groups. Sensitivity of all three indicators together was 0.31, but specificity was 1